Paul missionary, theologian - Reymond, Robert L. (Ross-shire, UK Christian Focus, 2000)
Includes bibliographcial references, indexes and maps.
Keywords: Paul, the apostle, Saint -- biography; Paul, the apostle, Saint -- theology